Coping with that thing called stress - Brigham Young University (Chicago : Encyclopaedia Britannica Educational Corporation, 1981)
Presents dramatic vignettes demonstrating both succesful and unsuccessful attemts to deal with stressful situations.
Keywords: Stress (Psychology) -- Case studies; Stress (Psychology) -- Congresses